BRAND MANAGEMENT IN THE DIGITAL AGE: STRATEGIES AND BEST PRACTICES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Brand management in the digital age has become increasingly complex and dynamic, requiring businesses to adopt new strategies and best practices to effectively navigate the digital landscape. This article examines the evolving role of brand management in the digital era, exploring key strategies and best practices for building, monitoring, and maintaining brand equity in the digital realm. By analyzing case studies and industry trends, this article provides insights into how businesses can leverage digital channels and technologies to enhance brand visibility, engage with consumers, and drive long-term brand loyalty.